Feasibility Study of Solar Power Plant in the Rectorate Building of Lampung University Using the Ongrid System - Khairudin; Ocazy Harun; Despa Dikpride (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2021)
This research aims to analyze the technical and economic feasibility aspects of the construction of solar power plants in the Rectorate building of Lampung University. Technical aspects are calculated how much electrical energy is generated, the number of components and systems used. Then the economic aspects are calculated using the net present value (NPV) and profitability index (PI) methods to determine profitable or detrimental investments in the future. The electrical energy generated by solar power plant is affected by solar radiation based on RetScreen data and the number of solar modules installed on rooftop buildings. The results of this study showed that the construction of solar power plant in the Rectorate building of the University of Lampung is feasible to built using ballast installation techniques and on-grid systems, based on economic aspect, it is feasible. Keywords: RetScreen, rooftop, on grid, Unila